Peran Inspektorat Daerah Dalam Melakukan Fungsi Pengawasan Pengelolaan Dana Desa di desa Bacu, Kecamatan Barebbo, Kabupaten Bone - Andi Mapparessa (Departemen Ilmu Pemerintahan Fisip Unhas, 2024)
Supervision of Village Fund management is an essential effort to establish transparent, accountable, effective, and corruption-free village governance. As the Government Internal Supervisory Apparatus (APIP), the Inspectorate plays a strategic role in ensuring that Village Fund management is carried out in accordance with applicable laws and regulations. This study aims to analyze the role of the Inspectorate in supervising Village Fund management in Bacu Village, Barebbo District, Bone Regency. The study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving informants from the Bone Regency Inspectorate and the Bacu Village Government. Data were analyzed using descriptive qualitative techniques through data collection, reduction, presentation, and conclusion drawing. The findings indicate that the Inspectorate's supervision of Village Fund management has been implemented through several stages, including inspection, investigation, testing, supervision implementation, monitoring and evaluation, preparation of Audit Reports (Laporan Hasil Pemeriksaan), and supervision of Village Fund allocation. Overall, these supervisory activities have been carried out in accordance with applicable regulations and have contributed to improving the accountability of Village Fund management. However, several challenges remain, including limited supervision budgets, inadequate competency of village officials, incomplete supporting documents, and delays in the follow-up of audit findings. Therefore, strengthening human resource capacity, enhancing coordination between the Inspectorate and village governments, and optimizing supervisory mechanisms are necessary to support more effective and accountable Village Fund management.